Exploring the professional development needs of nurse educators in Saudi Arabia: A cross-sectional survey - Mai Salem Alharsan; Amal Ismael Abdelhafez (Belitung Raya Foundation, 2023)
Background: Professional development for nurse educators is essential to ensure that nursing students receive high-quality education and can provide effective patient care. However, nurse educators in Saudi Arabia encounter numerous challenges, emphasizing the need for tailored career development opportunities. Objective: This study aimed to identify the professional development needs of nurse educators within Saudi university nursing programs. Methods: A quantitative cross-sectional survey was employed in April 2023, involving 121 nurse educators selected through convenience sampling. The study consisted of nursing colleges and departments at 15 government-operated Saudi universities. Data were collected on April 2023 through questionnaires and analyzed using descriptive statistics and correlational analysis. Results: Among participants, 45 (37.2%) had 6 to 10 years of teaching experience. Evaluating learning (76.9%) was the most frequently identified Professional Faculty Development Need in teaching skills. Writing articles and abstracts (73.6%) were commonly identified in scholarly development, while presentation software for teaching (79.3%) dominated technology use development. The most preferred method for taking a development program was 1-2-hour sessions (81%). Significant differences in professional needs based on years of academic experience and academic rank were observed (p <0.05). Conclusion: The study identified various terms related to nurse educators' perceived development needs. Educator development and educational specialists must consider both overlapping and unique requirements of different health science schools in planning professional development. Crucial skills highlighted in the study include cross-cultural teaching strategies, course design, large group teaching, conflict management, negotiation, and team-building for administrative work and career development.